COVID-19: A Systematic Review of the Transmissibility, Pathogenesis, Entry Factors, and Signature Immune Response - Deena Fayyad; Jessica L. Kelts; Tristan H. Nielson; Ibiere Lovelyn Epelle; Nicodemus C. Monear; Miguel T. G. Strawn; Benjamin N. Woerner; Besa Xhabija (MDPI AG, 2022)
Objectives: The emergence of coronavirus disease 2019 (COVID-19), caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has led to a global health calamity unprecedented in the modern world. The disease spread worldwide, and to date, there have been over 230 million confirmed cases of COVID-19, including approximately 4.7 million deaths. Mutant variants of the virus have raised concerns about additional pandemic waves and threaten to reverse our progress thus far to limit the spread of the virus. These variants include Alpha, Beta, and Delta (first reported in December 2020 in the United Kingdom, South Africa, and India, respectively) and Gamma (reported in January 2021 in Brazil). In some cases, countries have even reported a rise in daily cases higher than the first wave in March 2020. Given the rapidly evolving nature of COVID-19 and subsequent new findings and updates each day, this review article aims to comprehensively summarize the etiology, pathophysiology, and clinical features of SARS-CoV-2 infection. Methods: A systematic review of the literature was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines to gain insight into the transmissibility, pathogenesis, entry factors, and immune response of COVID-19. Specifically, Pubmed and Google Scholar databases were searched to identify any relevant articles. References within the included articles were reviewed. Published articles related to search criteria from the onset of the COVID-19 pandemic to March 2022 were included. Results: Viral transmissibility is predominantly affected by the modes of transmission, various mutations on the nucleocapsid protein and endoRNAse, gender, age, and other factors. The pathophysiological mechanism is generally unknown, although the clinical manifestations such as headache, loss of smell and taste, vomiting, diarrhea, multiorgan failure, and dermatological and cardiovascular complications are well documented. The progression of infection depends on the immunopathological response and the innate/adaptive immunity. Conclusion: Our review has summarized the latest knowledge about SARS-CoV2. However, as the pandemic continues to spread across the continents, there is an urgent need for more research on potentially emerging coronaviruses and the development of a universal coronaviruses vaccine to put the pandemic behind us.